Hydraulic conditions leading to exponential mine tailings delta profiles - P. H. Morris (The Institute of Materials, Minerals and Mining, 1905)
The exponential delta profile equation matches the profiles of a wide range of coal and metalliferous subaerial tailings deltas well, but the original model implies unrepresentatively low solids concentrations. A revision, based on analysis of the governing equations of mobile bed flows with high concentration values, has shown that for exponential delta profiles to form there must be quasi-steady, slowly varying flow and slow deposition as well as tailings with a log-uniform sorting-parameter distribution. Deposition on tailings deltas is slow and the flow in many natural streams and, by analogy, tailings deltas is quasi-steady and slowly varying; the assumption of such flow is justified by the strong congruence of the revised model and the available data. The predictions of the theoretical model are essentially unchanged but concentration and flow Froude number are now not explicitly limited